Management of Acute Apical Abscess Presenting with Rapid Extrusion of a Tooth: A Case Report - Parirokh, Masoud; Manochehrifar, Hamed; Sarhadi, Alireza (Iranian Endodontic Journal, 2025)
An acute apical abscess (AAA) is a rapid-onset inflammatory condition characterized by spontaneous pain, pus formation, and swelling, often resulting from pulp necrosis. Complications may include systemic manifestations and severe outcomes, such as tooth extrusion. This case report describes a rare instance of AAA causing rapid extrusion of a maxillary central incisor in a 17-year-old female. The patient presented with spontaneous pain and mobility of the extruded tooth, accompanied by localized swelling. Clinical and radiographic evaluations revealed pulp necrosis, an AAA, and apical bone rarefaction. Emergency treatment was initiated, including intracanal medication with calcium hydroxide and temporary splinting of the tooth. Subsequent treatment involved obturation with gutta-percha and sealer, followed by permanent restoration. Radiographic and clinical recalls up to 5 years demonstrated complete periapical healing, normal tooth mobility, and no recurrence of symptoms. Effective management, including timely root canal therapy and splinting, led to successful long-term outcomes. This case underscores the importance of prompt diagnosis and immediate, tailored treatment to manage AAA and prevent severe complications.